A small molecule inhibitor of Notch1 modulates stemness and suppresses breast cancer cell growth - Saran, Uttara; Chandrasekaran, Balaji; Tyagi, Ashish; Shukla, Vaibhav; Singh, Amandeep; Sharma, Arun K.; Damodaran, Chendil (Frontiers in Pharmacology, 2023)
Although breast cancer stem cells (BCSC) are well characterized, molecularly targeting and eradicating this sub-population remains a challenge in the clinic. Recent studies have explored several signaling pathways that govern stem cell activation: we and others established that the Notch1 signaling plays a significant role in the proliferation, survival, and differentiation of BCSCs. Earlier, we reported that a newly developed small molecule, ASR490, binds to the negative regulatory region (NRR: the activation switch of the Notch receptor) of Notch1. In vitro results demonstrated that ASR490 significantly inhibited BCSC (ALDH+ and CD44+/CD24-) and BC’s growth at nM concentrations, and subsequently inhibited the colony- and mammospheres-forming abilities of BCSCs and BCs. ASR490 downregulated the expressions of Notch intracellular domain (NICD: the active form of Notch1) and its downstream effectors Hey1 and HES1. Inhibition of NICD facilitated autophagy-mediated growth inhibition by triggering the fusion of autophagosome and autolysosome in BCSC. ASR490 was found to be non-toxic to healthy cells as compared to existing Notch1 inhibitors. Moreover, oral administration of ASR490 abrogated BCSC and BC tumor growth in in vivo xenograft models. Together our results indicate that ASR490 is a potential therapeutic agent that inhibits BC tumor growth by targeting and abolishing Notch1 signaling in BCSC and BC cells.